2010
DOI: 10.1021/ar100125j
|View full text |Cite
|
Sign up to set email alerts
|

Studies Leading to the Development of a Single-Electron Transfer (SET) Photochemical Strategy for Syntheses of Macrocyclic Polyethers, Polythioethers, and Polyamides

Abstract: Organic photochemists began to recognize in the 1970s that a new mechanistic pathway involving excited-state single-electron transfer (SET) could be used to drive unique photochemical reactions. Arnold's seminal studies demonstrated that SET photochemical reactions proceed by way of ion radical intermediates, the properties of which govern the nature of the ensuing reaction pathways. Thus, in contrast to classical photochemical reactions, SET-promoted excited-state processes are controlled by the nature and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 60 publications
(88 reference statements)
1
50
1
Order By: Relevance
“…In principle, radical intermediates in ET-promoted reactions have a tendency to participate in further ET processes to generate ionic species when stoichiometric amounts of redox reagents are used (Scheme 1) [1–10]. In contrast, radical intermediates formed by a photoinduced ET (PET) are less likely to undergo these secondary reactions, because steady-state concentrations of PET-generated redox reagents are low [11–19]. When radical intermediates and ions derived from their precursor radical ions undergo different rearrangement reactions, it is often possible to distinguish respective reaction pathways of radicals and ions by examining the product distributions of the reactions of substrates that contain appropriate probe moieties (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, radical intermediates in ET-promoted reactions have a tendency to participate in further ET processes to generate ionic species when stoichiometric amounts of redox reagents are used (Scheme 1) [1–10]. In contrast, radical intermediates formed by a photoinduced ET (PET) are less likely to undergo these secondary reactions, because steady-state concentrations of PET-generated redox reagents are low [11–19]. When radical intermediates and ions derived from their precursor radical ions undergo different rearrangement reactions, it is often possible to distinguish respective reaction pathways of radicals and ions by examining the product distributions of the reactions of substrates that contain appropriate probe moieties (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[5,[6] In certain cases these bonds are sufficiently weakened such that they undergo spontaneous scission, resulting in the formation of two new intermediates – a neutral free radical and a carbocation. While pioneering studies from Arnold, [7] Floreancig, [8] Mariano, [9] and Albini [10] have demonstrated the feasibility and value of these methods, mesolytic cleavage-based strategies for simple carbocation generation remain underutilized.…”
mentioning
confidence: 99%
“…These fragmentation reactions produce neutral radicals, which then participate in typical radical reactions, including C–C bond formation and addition to unsaturated centers. Because of their importance, α-heterolytic fragmentation reactions of radical anions and cations have been intensively studied from synthetic and mechanistic perspectives [11–34]. …”
Section: Reviewmentioning
confidence: 99%
“…Previous studies [3134 62–67] in our laboratories resulted in the development, mechanistic elucidation, and synthetic application of various kinds of SET-promoted photocyclization reactions of α-trialkylsilyl donor-linked imide acceptor systems and led to an understanding of the factors controling the chemical selectivities and efficiencies. For example, we have demonstrated that intramolecular SET-photochemical reactions of linked α-trimethylsilyl n-electron donor-phthalimides/naphthalimides produce functionalized macrocyclic poly-ethers, -thioethers, -amides, and -peptides via the intermediacy of interconverting zwitterionic biradicals 21 and 22 .…”
Section: Reviewmentioning
confidence: 99%